Pornography and Masturbation Addictions through the Lens of Self-Help: Insights from NeverFap Academy Members - Kara, Hüseyin Zahid; Karaman, Hakan; Yaman, Ömer Miraç (Addicta: The Turkish Journal on Addictions, 2025)
This qualitative study analyzes the experiences of individuals struggling with pornography and masturbation addiction, focusing on their engagement with NeverFap Academy, a peer-based self-help platform in Türkiye. Semi-structured interviews were conducted with participants who actively used the NeverFap’s resources, including thematic online camps, WhatsApp support groups, YouTube videos, and blog content. Thematic analysis identified three major themes: encountering addiction, effects on life, and fighting addiction. Findings revealed that initial exposure to pornography, often accompanied by compulsive masturbation, typically occurred during adolescence, influenced by peers and easy online access. Participants reported significant negative effects in psychological, academic, social, and familial domains, including guilt, concentration problems, social withdrawal, and strained relationships. NeverFap Academy was seen as instrumental in promoting recovery through structured routines, community support, and value-based motivation. The platform not only helped reduce addictive behaviors but also fostered personal growth and a renewed sense of purpose. While the study shows the value of community-based efforts in addressing addiction, its findings are limited to the NeverFap community. Future research should compare self-help initiatives like NoFap, NeverFap, and Jiese and explore their integration into broader mental health and policy frameworks.
Keywords: Addiction; masturbation; pornography; self-help group